Enterococcus faecalis Escapes Complement-Mediated Killing via Recruitment of Complement Factor H. (6th May 2019) - Ali, Youssif M; Sim, Robert B; Schwaeble, Wilhelm; Shaaban, Mona I
Abstract: Background: Enterococcus faecalis is considered to be the most important species of enterococci responsible for blood stream infections in critically ill patients. In blood, the complement system is activated via the classical pathway (CP), the lectin pathway (LP), or the alternative pathway (AP), and it plays a critical role in opsonophagocytosis of bacteria including E faecalis . Methods: In a mouse model of enterococcus peritonitis, BALB-C mice were challenged with a high dose of E faecalis 12 hours after intraperitoneal administration of anti-Factor H (FH) antibodies or isotype control. Four hours later, control mice developed higher bacterial burden in blood and organs compared with mice treated with anti-FH antibodies. Results: We demonstrate that complement recognition molecules C1q, CL-11, and murine ficolin-A bind the enterococcus and drive the CP and the LP in human and mouse. We further describe that E faecalis evades the AP by recruitment of FH on its surface. Our results show a strong C3b deposition on E faecalis via both the CP and the LP but not through the AP. Conclusions: These findings indicate that E faecalis avoids the complement phagocytosis by the AP via sequestering complement FH from the host blood. Abstract : Enterococcus faecalis avoids complement-mediated phagocytosis by the alternative pathway via sequestering complement FH from the host blood, whereas opsonophagocytosis is mediated via both the classical and the lectin pathways.